2021
DOI: 10.33828/sei.v32.i4.11
|View full text |Cite
|
Sign up to set email alerts
|

An Active Learning Framework for Ecological Intelligence: Using Activities of Multiple Intelligences to Achieve Ecological Awareness

Abstract: The current paper aimed to identify the relation between ecological intelligence (EI) and the types of multiple intelligences (MI); and pointed out how ecological awareness could be raised through activities of MI. Data was gathered from the freshman students (N = 68) who studied at the Department of Primary Education. Four measures were used in this case study: interviews, multiple intelligence inventory (MII), ecological intelligence scale (EIS), and students' 5-min notes. Correlation analysis was used to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, Ilela et al (2021) found that EI was significantly related to PEB. EI is a factor potentially leading to environment‐friendly actions (Güven & Uyulgan, 2021). In another study by Mulyana et al (2021), increased EI was associated with behaviours that contribute to protecting the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ilela et al (2021) found that EI was significantly related to PEB. EI is a factor potentially leading to environment‐friendly actions (Güven & Uyulgan, 2021). In another study by Mulyana et al (2021), increased EI was associated with behaviours that contribute to protecting the environment.…”
Section: Introductionmentioning
confidence: 99%